1984
DOI: 10.1203/00006450-198411000-00129
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor development of children with congenital hypothyroidism (The greek screening programme)

Abstract: p i t a l des Enfants. 168. Cours de 1'Argonne-33077 Bordeaux-F M E-95 P l a s m Thy,l obul i n (Tg) i n hypothyroid children under L. Thyroxine therapy (L.T.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

1994
1994
2004
2004

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…The New England Congenital Hypothyroidism Collaborative's study and some other studies have found either normal mean IQs,3,17,27,28 an apparent absence of a correlation with disease severity,3,17 or lower IQs in subjects with low thyroxine and high thyroid stimulating hormone concentrations during treatment3,7,17 and have attributed intellectual impairment to either delayed treatment or under treatment. *RF 17,26 Though we too found that children with low thyroxine values (<103 nmol/l, equivalent to 8 mu g/dl as defined in a previous study3,17 during treatment tended to have a lower mean IQ, we could find no independent association between low thyroxine concentration and outcome after allowing for the effect on IQ of social class and severity.…”
Section: Discussionmentioning
confidence: 97%
“…The New England Congenital Hypothyroidism Collaborative's study and some other studies have found either normal mean IQs,3,17,27,28 an apparent absence of a correlation with disease severity,3,17 or lower IQs in subjects with low thyroxine and high thyroid stimulating hormone concentrations during treatment3,7,17 and have attributed intellectual impairment to either delayed treatment or under treatment. *RF 17,26 Though we too found that children with low thyroxine values (<103 nmol/l, equivalent to 8 mu g/dl as defined in a previous study3,17 during treatment tended to have a lower mean IQ, we could find no independent association between low thyroxine concentration and outcome after allowing for the effect on IQ of social class and severity.…”
Section: Discussionmentioning
confidence: 97%
“…Since the adverse effects of hypothyroidism may develop during thyroxin withdrawal, some authors have suggested reducing the dose of thyroxin by 50% instead of discontinuing treatment altogether (1). On the other hand, since most patients with NTH recover within several months, several medical institutions, particularly in Europe where the prevalence of NTH is considerably higher than in North America, attempt the withdrawal of thyroxin replacement at approximately 2 y of age to abbreviate the duration of the treatment burden for parents and patients (15,16). Therefore, we believe that it would be preferable, during treatment withdrawal in high-risk patients, to reduce the dose of thyroxin by only 50% to avoid the development of serious consequences of hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to descriptions from other studies where the hypothyroid infants had the typical appearance of a cretin 12 . We assume that this is due to well-controlled thyroid of the children affected 6,7 . In Greece, a similar program was initiated in the early 80s on a nationwide basis.…”
Section: Discussionmentioning
confidence: 99%